Evaluation of Wound Healing Activity of 80% Methanol Root Crude Extract and Solvent Fractions of Stephania abyssinica (Dill. & A. Rich.) Walp. (Menispermaceae) in Mice - Yiblet TG; Tsegaw A; Ahmed N; Dagnew SB; Tadesse TY; Kifle ZD (Dove Medical Press, 2022)
Tesfagegn Gobezie Yiblet,1 Asegedech Tsegaw,2 Nejat Ahmed,3 Samuel Berihun Dagnew,1 Tesfaye Yimer Tadesse,1 Zemene Demelash Kifle2 1Department of Pharmacy, College of Medicine and Health Sciences, Debre Tabor University, Debre Tabor, Ethiopia; 2University of Gondar, College of Medicine and Health Sciences, School of Pharmacy, Department of Pharmacology, Gondar, Ethiopia; 3Department of Pathology, School of Medicine, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Tesfagegn Gobezie Yiblet, Tel +251935462779, Email tesfaxx@gmail.comBackground: The root of Stephania abyssinica (Dill. and A. Rich.) Walp. (Menispermaceae) is traditionally used to treat wounds. Despite the fact that there have been in vitro studies and claims supporting wound healing, there has been no scientific data on the in vivo wound healing activities of the root of S. Abyssinica.Objective: The aim of the study was to evaluate the wound healing activity of 80% methanol root extract and solvent fractions of S. Abyssinica in mice.Methods: The roots of S. Abyssinica were air dried, ground and macerated by 80% methanol three times successively. The crude extract was fractionated by water, hexane and ethyl acetate separately. The acute dermal toxicity test was done by applying 2000 mg/kg of the 10% w/w crude extract. Wound healing activity of crude extract was evaluated on excision, incision and burn wound models, while the fractions were evaluated on excision wound model only.Results: In mice, an acute dermal toxicity test of 2000 mg/kg of the 10% w/w crude extract was found to be safe. The 10% w/w crude extract ointment (CEO) produced significant (p < 0.001) wound contraction from 4th to 16th post wounding days, and the 5% w/w CEO were significant (p < 0.01) wound contraction on 10th post wounding day as compared to simple ointment (SO) treated group on excision wound. On burn wound models, the CEO showed highly significant (p < 0.001) from the 6th post wounding days onwards. The tensile strength was increased significantly (p < 0.001) by the CEO treated mice as compared to the untreated group and SO group.Conclusion: The data obtained from this study showed 80% methanol crude extract, the aqueous and the 10% w/w ethyl acetate fraction possessed better wound healing activities, and decreased period of epithelialization.Keywords: wound healing, Stephania abyssinica, wound models, Ethiopia